The host resistance locus Cmv1Ly49h regulates global gene expression in spleen DX5+ NK cells in response to murine cytomegalovirus infection - Kim, Kwangsin (University of Ottawa (Canada), 2006)
In mice, the Cmv1/Ly49h locus expressed on Natural Killer (NK) cells determines innate resistance to Murine Cytomegalovirus Virus (MCMV). NK cells provide the first line of defence against infections and tumors through cytokine production or direct cytotoxicity. Acquisition of MCMV resistance in transgenic mice expressing Ly49H, hereafter FVB-Tg (Ly49h), demonstrated the critical role of Ly49H in clearance of the infection, and provided an ideal model to characterize the role of NK cells in host defence. The scoring of viral titers in the visceral organs of Ly49H transgenic (FVB-Tg (Ly49h)) mice and their MCMV-susceptible counterparts, FVB, indicated a tissue specific effect of Ly49H independent of genetic background in spleen, lung, kidney and thymus. In the liver, the presence of Ly49H was associated with increased numbers of inflammatory foci, suggesting that Ly49H may facilitate localization of NK cells to the vicinity of infected cells. To identify genes critical to the initial control of virus replication, comparative gene expression analysis of explanted spleen NK cells from FVB-Tg (Ly49h) and FVB mice was carried at 36 hours post-infection. This allows for the onset of Ly49H related mechanisms of host resistance. In contrast to whole spleen samples, RT-PCR from purified NK cells from either mouse strain did not detect MCMV gene expression, indicating that NK cells are not productively infected. Out of 16,000 genes analyzed by microarray, 35 showed greater than 2.5-fold expression difference between resistant and susceptible mice. Genes involved in NK cell proliferation, cytotoxicity and in cell-mediated immunity, such as the early T lymphocyte activation-1 gene (Eta-1 or osteopontin), showed enhanced expression in NK cells from resistant mice. On the other hand, NK cells from susceptible mice showed increased expression of pro-inflammatory cytokines such as IFN-gamma, MIP2, and TNF-associated receptors, indicating that antiviral cytokines are not sufficient to control viral replication in the absence of Ly49h, and that direct killing of virus-infected cells by NK cells expressing Ly49H is required for successful clearance of MCMV. To characterize the response of NK cells during MCMV clearance further, gene expression patterns were studied in FVB-Tg (Ly49h) during the course of infection. Out of 22690 genes analyzed, the expression of 225 genes was significantly changed at 3 days post-infection, when the effect of Cmv1/Ly49h is strongest and the viral load is highest. At later time points, the number of genes affected and the level of gene expression gradually returned to normal, in parallel with a decrease in viral titer, indicating that altered expression patterns co-varied with viral burden. More than 50% of the genes upregulated were involved in cell proliferation, metabolism, and transcription, while about 15% were involved in NK cell cytotoxic function, indicating that NK cell blastogenesis and direct killing of infected cells are crucial for MCMV-resistance. Altogether, our results indicate that the differential pattern of expression between resistant and susceptible mice depends on the presence or absence of Ly49h as well as on signals emanating from productively infected cells, such as macrophages and dendritic cells. Genes differentially expressed on MCMV-susceptible NK cells may serve as useful biomarkers for HCMV susceptibility in risk populations, graft recipients in particular.
Keywords: Biology, Virology.; Health Sciences, Immunology.